AUDIT STRATEGI TATA KELOLA IT PADA STMIK BINA NUSANTARA JAYA LUBUKLINGGAU MENGGUNAKAN FRAMEWORK COBIT 5 - Puspita Dewi Setyadi; Edi Surya Negara (CogITo Smart Journal, 2022)
In the implementation of academic and non-academic activities STMIK Bina Nusantara Jaya Lubuklinggau has integrated and implemented the use of information technology through SIAKAD ( Academic System) . To be able to carry out the implementation of information technology according to service quality orders and a framework which later can help an organization to be able to improve or improve technology governance in accordance with IT governance standards. Information technology governance, in its role, has many tools to carry out assessments and measurement indicators to help universities. In this study, the author uses cobit 5 famework as an IT governance standard. In the COBIT 5 process, the author only uses the APO 11 and MEA 01 processes. The APO11 (Quality of Service) process has 6 attributes that are used and MEA (Monitor, Evaluate, assess conformance and Conformance) has 5 attributes that are used. There is a gap value between attributes, current conditions and what is expected. The results of the gap analysis obtained in the APO11 and MEA processes still have numbers 1 and 0. The results of the gap number 1 indicate that the current condition is still not good with the expected conditionsKeyword- Audit,Governance, Cobit 5, APO,MEA